Realizing Excellent Thermoelectric Performance of Sb2Te3 Based Segmented Leg with a Wide Temperature Range Using One‐Step Sintering. (27th December 2019) - Xie, Liangjun; Qin, Haixu; Zhu, Jianbo; Yin, Li; Qin, Dandan; Guo, Fengkai; Cai, Wei; Zhang, Qian; Sui, Jiehe
Abstract: To achieve a wide temperature range and a high figure‐of‐merit, segmented assembling is considered as the most effective method based on optimized low‐temperature and medium‐temperature thermoelectric materials. In this work, divalent magnesium (Mg) as acceptor doping in both Bi0.5 Sb1.5 Te3 and indium (In) alloyed Sb2 Te3 play an important role in improving thermoelectric performance, including enhanced power factor by balancing the electrical conductivity and Seebeck coefficient, reduced bipolar thermal conductivity by delaying occurrence of intrinsic excitation, and reduced lattice thermal conductivity due to point defects. Finally, both the figure‐of‐merit ( ZT ) value and the corresponding operating temperature range are improved. Typically, Mg0.01 Bi0.5 Sb1.49 Te3 with a ZT ave of 1.16 from 300 to 520 K and a ZT ave of 0.84 for Mg0.02 In0.1 Sb1.88 Te3 from 500 to 680 K are obtained. To further obtain wide‐temperature high ZT value, p‐type Mg0.01 Bi0.5 Sb1.49 Te3 /Mg0.02 In0.1 Sb1.88 Te3 segmented leg with excellent interface bonding and extremely low contact resistivity is successfully fabricated by only one‐step sintering process. The corresponding average ZT value is up to 1.02 with a broad temperature range from 300 to 680 K, and a maximum theoretical conversion efficiency of 12.7% with a temperature difference of 380 K is obtained. This provides guidelines for high efficiency thermoelectric devices. Abstract : Mg acceptor doping improves the thermoelectric properties of Bi0.5 Sb1.5 Te3 and Indium (In) alloyed Sb2 Te3 by suppressing bipolar effect. For the Mg0.01 Bi0.5 Sb1.49 Te3 /Mg0.02 In0.1 Sb1.88 Te3 segmented leg fabricated only through one‐step sintering, the average figure‐of‐merit is up to 1.02 from 300 to 680 K, and the calculated theoretical conversion efficiency is up to 12.7% under the temperature difference of 380 K.